(untitled) (PHARMACON, 2013)
ABSTRACT Suji (Dracaena angustifolia Roxb.) has been used empirically by the people of North Sulawesi to cure the disease. Flavonoids and steroids in suji leaves suspected to have antiinflammatroy effects. This study aims to examine the antiinflammatory effects of ethanol extract from suji leaves (Dracaena angustifolia Roxb.) on edema of white males wistar foot induced with 5% white egg solution, and to determine an effective dose of extract to decrease the edema volume ofrat foot. The test was done using rat hind paw edema or esthablished an artificial inflammation in left foot of white male rats.The treatments were carried out on five groups, the positive control group was administered with diclofenac sodium, the negative control group was administered with aquadest, and the extract groups were administered with 100 mg/KgBB, 300 mg/KgBB and 1000 mg/KgBB of suji leaf extract. Edema volume were measured every hour for 7 hours using a glass tube. The average of edema volume (mL) and time (hour) was plotted in a curve to form Area Under Curve (AUC). The AUC values were used to calculate the percentage of antiinflammatory on each group compared to the negative control group. Obtained data were analyzed by one-way ANOVA followed by LSD test with confident level was 0,05. The result of this study indicate that suji leaf can reduce edema volume of rat foot that induced with 5% white egg solution and antiinflamatory of ethanol extract from suji leaf 100 mg/KgBB by 33,19 %, 300 mg/KgBB by 14,04 % and 1000 mg/KgBB by 5,80 %. Keywords: Suji(Dracaena angustifolia Roxb.), antiinflammatory, edema